Argumentation in The Science Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Proper argumentation in the science classroom promotes conceptual understanding of complex phenomena, while also giving learners the ability to participate in authentic scientific reasoning. This methodical process that is often skipped in science classrooms gives students a chance to practice testing claims, refining their positions, and effectively communicating evidenced-based ideas to their peers. These methods of investigation teach proper scientific reasoning and communication skills that will simultaneously promote higher-order student thinking. The current studies suggest an increasing need for teachers to support their students in creating and enriching concept schemas through modeling questions/proper arguments, providing prompts, eliciting prior knowledge, guiding investigation, and encouraging reflective discussions.
Keywords: Argumentation; Science process skills; Scientific critique; reasoning; group discussion; questioning